PERAN KEBIJAKAN FISKAL PEMERINTAH INDONESIA DALAM MENGHADAPI RESESI EKONOMI AKIBAT DAMPAK PANDEMI COVID-19 - Angeline Wijayanti; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2023)
This study aimed to the policies of the Indonesian government in facing the economic recession due to Covid-19. This study is a qualitative research using the case study method. This study examines the experience of Indonesian government policies as a country that has faced through economic crises in the past and analyzes whether this fiscal policy can be adopted as a strategy in dealing with an economic recession due to the Covid-19 pandemic. The study uses documentation, observation, literature study and assessment techniques on the analysis of the Indonesian government's fiscal policy in facing an economic recession due to the impact of the Covid-19 pandemic. This study shows that the government plays a role in increasing state expenditure and providing tax incentives to boost the economy out of an economic recession. This study provides a new perspective on the policy analysis of the role of the Indonesian government in dealing with the economic recession due to the Covid-19 pandemic.